TOKOH AGAMA DAN POLITIK: BIOGRAFI ABI LAMPISANG, 1962-2017 - Rizqal Fajri; Mawardi .; zulfan . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
Abi Lampisang's figure is very interesting to study because of his prominent role and contribution in the field of religious and political education in Aceh As a religious figure Abi Lampisang has contributed to educating students and the community through the dayah he leads, while in the political arena Abi Lampisang has been heavily involved in various elections at both the district and provincial levels. The study, entitled "Religious and Political Figures (Biography Abi Lampisang, 1962-2017)", aims to explain (1) biography of Abi Lampisang, 1962-2017, (2) explain the factors that influence Abi Lampisang to become a religious and political figure (3) the role of Abi Lampisang in the development of Islamic education, 1983-2017, and (4) the political life of Abi Lampisang, 1996-2017. This study uses a qualitative approach and historical method which consists of five steps namely the selection of themes, heuristics, verification, interpretation and historiography. Data collection techniques are carried out with interviews, documentation and literature studies. The results of the research show that Abi Lampisang was born on September 15, 1962, his father Tgk. Sheikh Abdullah Bin Ahmad and his mother Marziyah Bint Fatimah. He is the third child of 10 siblings. Abi Lampisang obtained his first Islamic education from his parents then continued religious education in the Ruhul Fata Dayah 1972, in 1976 at the MUDI Mesra Dayah and 1982 to Labuhan Haji Darussalam Dayah. His Islamic religious thought was strongly influenced by environmental factors from various educational institutions where he studied. His political thinking was influenced by participation in GAM and bigotry against Tgk. Hasan di Tiro. Abi Lampisang's role in the development of Islamic religious education is to become the leader of Al Muhajirin Dayah from 1983-2018. Abi Lampisang's role in politics in 1990-2017 was marked by his participation in various Acehnese political institutions such as the establishment of the Aceh Daulat Party (PDA), Aceh Rabithat Thaliban (RTA), the Aceh Dayah Ulema Association (HUDA). In 1999, he acted as chairman of GAM's struggle and advisor, participated in the 2012 Aceh Regional Election as a gubernatorial candidate, and was involved in regional elections at the district level.Keywords: Abi Lampisang, Religious Figures and Political Figures.